Lecturers’ Perceptions of Integrating Islamic Environmental Ethics into Sustainability Education - Laylay Hasan; Zaynab Omar; Karima Elhaj; Abdulrauf Atia; Entisar Alatrish; Fatima Alsaeh; Mohamed Elbi (Saniya Institute, 2025)
This study examines lecturers’ perceptions of integrating Islamic environmental ethics in sustainability education in Libyan higher education institutions. Using a mixed-methods design, survey data were collected from 150 lecturers at the University of Zawia using a 21item questionnaire covering conceptual understanding, perceived importance, teaching practices, perceived outcomes, institutional support, and challenges/professional needs. Semi-structured interviews with 10 lecturers were conducted to contextualize and explain the quantitative patterns. Quantitative findings showed strong support to the conceptual coherence and importance of Islamic environmental ethics for sustainability education, with high perceived student outcomes, but only moderate levels of reported teaching practices. Institutional support received the lowest ratings and showed high variability, while professional development and time constraints emerged as notable needs. Qualitative themes indicated that lecturers commonly anchor sustainability in Islamic concepts such as khilafah (stewardship), amanah (trust), mizan (balance), and harm prevention, and report higher student engagement when sustainability is framed as moral accountability and identity-consistent learning. However, implementation was constrained by limited structured programs, scarce teaching materials, lack of locally grounded Libyan case resources, and challenges in assessing ethical learning outcomes. The study suggests implementation pathway from ethical integration to pedagogical translation and institutional enabling conditions, offering implications for curriculum design, staff development, and policy to support scalable integration in Libyan universities.